A Methods engineering study on Stiletto and More - Custodio, Margarett S.; Dunuan, Lara Mia s.; Lim, Loubert Peter A.; Maputol, Arlene T. (Diliman, Quezon City College of Engineering, 2002)
Stiletto & More is a shoe factory located in Antipolo City. It was established in 1999 by Vilma S. Enriquez and Rachel C. Veloso. The main product line of the company is ladies? footwear. They manufacture step-ins, sandals, high-heeled shoes, stilettos, mules and other styles for ladies shoes. At present, they have contracts with three famous shoe distributors namely Via Venetto, Francesco and Sundance. This study has several objectives. These are: (1) to trace the steps in producing ladies? footwear, (2) to search for shoe production problems and their causes, (3) to analyze these problems using methods engineering concepts, (4) to assess the plant?s layout and operations as a whole and its relation to productivity and (5) to offer alternatives that may improve the production using analytical tools. To accomplish these goals, the group did plant visits, interviews with management and the workers, observations within and outside the plant and also researches. From observations and interviews that the group did during their plant visits, the several problems that the company commonly encountered were identified. These are slow production, frequent machine failure, use of wrong materials, production errors and flaws in pattern, uncooperative workers and others. Due to lack of time to cover all the problems, the group focused on three problems that were obtained using tools learned from their methods engineering class. These problems are poor machine maintenance, late delivery of supplies and complicated design of patterns. From the analysis made, the group came up with the following proposals: 1) For the poor machine maintenance problem, the group proposed the implementation of weekly in-house maintenance and ?how to use? guidelines and precaution posters. 2) For the delay of delivery of supplies, the group proposed to organize their present storage facility and the introduction of an inventory system 3) And for the complexity of design of patterns, the group proposed the purchase of a magnifying lens and thorough inspection of the finished patterns. After the recommendations, the group also discussed several areas for further study.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Stiletto & More; Footwear industry; Systems analysis